A aplicação do princípio da solidariedade pelo Supremo Tribunal Federal entre os anos de 1988 e 2021:entre o direito à proteção previdenciária e o dever de contribuir - Costa, Victor Ribeiro da (2022)
This research deals with the application of the solidarity by Brazilian's Supreme Court (Federal Supreme Court) from 1988 to 2021 and aimed to analyze how (with what argumentative pattern quality) this incidence happened and what was this norm's role on Court decisions. This subject is relevant because solidarity is elementary for equating the tension between the Welfare State and the Tax State, translated to social security field as a tension between social security rights and the duty of contributing to a contributory pension system that, despite its solidarity features, also needs to maintain a financial and actuarial balance (according to articles 40 and 201 of the Brazilian Federal Constitution). Regardless of its relevance, the judicial application of the solidarity principle is still being neglected as a research theme and stands as a scientific blind spot on this matter, which reinforces the necessity of investigating this question. For so, this research utilized the hypothetic-deductive method and raised the initial hypothesis the idea that this norm would be used in opinionated and poorly systematic arguments (RODRIGUEZ, 2013), also producing faltering and contradictory effects. Testing it required bibliographic and empirical (jurisprudential) research, with quantitative and qualitative approaches. On the first step, a literary (bibliographical) revision took place for comprehending the norm, its application context, and the Court decisions patterns. The second part consisted of an exploratory study of the quantitative tendencies of this application, especially its chronological evolution, kinds of court cases, litigants and winners, related social security themes related to it, associated norms, effective functions, and application modalities. In the end, the third part of this research studied the norm incidence in three paradigmatic cases (the Declaratory Action of Unconstitutionality 3105 and the Extraordinary Appels 827.833/SC and 593.068/SC). Doing so, it aimed to comprehend with what argumentative quality this principle was used and what its role on cases solution. At last, it was possible to corroborate the hypothesis partially. Even though the Court applies solidarity in a casuistic and poorly systematic (faltering) way, the research was not capable of identifying an argumentative pattern strictly opinative since the heterogeneous judges' opinions (some of them were even systematic).